The effect of the ‘M’ Technique® massage on physiological parameters in preterm neonates: a randomized controlled trial study - Mona Alinejad-Naeini; Farshad Heidari-Beni; Parisa Mohagheghi; Soroor Sohrabi; Soraya Shojaee Jeshvaghanie (Journal of Pediatric and Neonatal Individualized Medicine, 2022)
Introduction: Preterm birth is one of the major health problems in developed and developing countries. The ‘M’ Technique® is a gentle, structured, stroking relaxation massage technique, which aims to reduce stress in preterm neonates in the Neonatal Intensive Care Unit (NICU) that cannot tolerate conventional massage techniques. Evidence consistently suggests that the ‘M’ Technique® is a safe non-medical intervention. The aim of this study was to examine the effect of the ‘M’ Technique® on physiological parameters of preterm neonates admitted to the NICU.